Enthalpy and internal energy : liquids, solutions and vapours - Letcher, T. M.; Wilhelm, Emmerich (Royal Society of Chemistry, 2018)
"Containing the very latest information on all aspects of enthalpy and internal energy as related to fluids, this book brings all the information into one authoritative survey in this well-defined field of chemical thermodynamics."--Page 4 of cover
Keywords: Gases.; Liquids.; Thermodynamics.; Enthalpy.; Gas.; elektronické knihy; electronic books